2016
DOI: 10.17577/ijertv5is030484
|View full text |Cite
|
Sign up to set email alerts
|

Development and Quality Evaluation of Yoghurt Fortified with Pineapple, Apple and Sweet Lemon Juice (Fruit Yoghurt)

Abstract: Yoghurt or dahi is consumed worldwide for its nutritional and health benefits. The research was conducted to prepare yoghurt incorporating different fruit juices and also to evaluate their quality characteristics. For this purpose, plain yoghurt and fruit yoghurts were prepared from whole milk of buffalo by adding different levels of fruit juice (5%, 10% and 15%) of different fruits (pineapple, apple and sweet lemon) except plain one in which fruit juice was not added and inoculating with strain of lactic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…This is due to higher content of total solids. This was in agreement with the results published for yoghurt enriched with grape juice (Hossain et al2012) and pineapple juice Gangwar et al (2016).…”
Section: Total Solidssupporting
confidence: 94%
“…This is due to higher content of total solids. This was in agreement with the results published for yoghurt enriched with grape juice (Hossain et al2012) and pineapple juice Gangwar et al (2016).…”
Section: Total Solidssupporting
confidence: 94%
“…The yogurt drink blended with 9% pineapple pulp contained the highest TS while it decreased with fruit added as TS content of pineapple itself are higher than milk. The results of Amadou et al (2016) and Gangwar et al (2016) confirming the obtained results.…”
Section: Chemical Composition Of Beveragessupporting
confidence: 84%
“…The total acceptability indicated that control samples had the highest degrees. Gangwar et al (2016) prepared plain yoghurt and fruit yoghurts from whole milk of buffalo by adding different levels of fruit juice (5%, 10% and 15%) of pineapple. Yoghurts fortified with 5% and 10% pineapple juice were good in smell and taste; yoghurts with 5% pineapple juice good in body and consistency; Yoghurts with 5% and 10% pineapple juice, were good in colour and texture; however 10% pineapple juice yoghurt being the best among all yoghurts.…”
Section: Chemical Composition Of Beveragesmentioning
confidence: 99%
“…Gangwar et al. (2016) observed higher acidity and lower pH of yoghurt incorporated with apple juice. They also reported that an increase in apple juice concentration in yoghurt increased acidity.…”
Section: Resultsmentioning
confidence: 99%